(untitled) (Analysis in Theory and Applications, 2021)
In this paper, we compare the mutual multifractal Rényi dimensions to the mutual multifractal Hausdorff and pre-packing dimensions. We also provide a relationship between the mutual multifractal Rényi dimensions of orthogonal projections of a couple of measures (μ, u) in R^n. As an application, we study the mutual multifractal analysis of the projections of measures.